Analisis Pergerakan Harga Saham untuk Mendeteksi Adanya Noise Atau Kedatangan Informasi di Bursa Efek Indonesia - Kartini -; Kurnia Yuspita (Jurnal Aplikasi Bisnis, 2016)
This study aimed to test the presence of noise or the arrival of information between non-trading period returns and trading period with prior periods. The data used are secondary data from the companies listed in LQ45for 2009 and 2011. The sample in this study wasl03 companies. Analysis tools used to test the hypothesis is auto correlation. Results of this study indicate that the price movement of shares between non-trading period and the period of trading in the stock exchanges in Indonesia caused by noise and arrival information. Correction caused by the noise made during the trading period. Based on company size, sales volume up and down market conditions, the price correction caused by the noise made during the trading period. Unless quintile based on trading volume, because the price correction caused by the noise made during non-trading periods.